Identification of an N-terminal Truncation of the NF-κB p65 Subunit That Specifically Modulates Ribosomal Protein S3-dependent NF-κB Gene Expression - Wier, Eric M. (American Society for Biochemistry and Molecular Biology, 2012)
NF-κB is a pleiotrophic transcription factor that plays a prominent regulatory role in various cellular processes. Although previous efforts have focused on its activation, how NF-κB selects specific target genes in response to discrete signals remains puzzling. In addition to the well defined Rel protein components of NF-κB, the ribosomal protein S3 (RPS3) was identified to be an essential component of specific NF-κB complexes. RPS3 synergistically interacts with the NF-κB p65 subunit to achieve optimal binding and transactivation of a subset of NF-κB target genes, thus providing regulatory specificity. Emerging evidence suggests an important role for the RPS3-p65 interaction in context-specific NF-κB gene transcription. The food-borne pathogen Escherichia coli O157:H7 impacts the transcription of a subset of NF-κB target genes encoding proinflammatory cytokines and chemokines in host cells by preventing the nuclear translocation of RPS3, but not p65. The N terminus of p65 is crucial for RPS3 binding. Although several p65 N-terminal fragments are generated by either protease cleavage or alternative mRNA splicing under certain pathophysiological conditions, the role of these fragments in modulating NF-κB signaling, in particular RPS3-dependent selective gene transcription, has not been fully characterized. Here we report that an N-terminal fragment of p65 (amino acids 21–186) can selectively modulate NF-κB gene transcription by competing for RPS3 binding to p65. This 21–186 fragment preferentially localizes in the cytoplasm where it delays stimuli-induced RPS3 nuclear translocation, without affecting the nuclear translocation of p65. Our findings thus uncover a new cytoplasmic function for the N-terminal domain of p65 and provide a novel strategy for selective inhibition of NF-κB gene transcription.